The effect of consuming candy containing gambir (Uncaria gambir) extract on salivary pH: Pengaruh konsumsi permen yang mengandung ekstrak gambir (Uncaria gambir) terhadap pH saliva - Dewi, Siti Rusdiana Puspa; Handayani, Pudji; Hestiningsih, Tyas; Angraini, Mona Rizki (Makassar Dental Journal, 2025)
Candy is a type of food that contains sugar which is high in calories. Candy consumption can lower the pH of saliva, which can trigger dental caries. Gambir (Uncaria gambir) is a type of plant that contains active compounds catechins and tannins, which can inhibit the colonisation of acid-causing bacteria in the oral cavity. This study aimed to determine the effect of gambir can-dy consumption on salivary pH; an experimental study with a pretest-posttest approach. The research subjects were 25 Sriwi-jaya University students, whose saliva samples were taken as much as 5 mL before and after consumption of candies containing gambier extract; using the spitting method and measured with a digital pH meter. Paired t-test was conducted for data analysis which showed that there was a significant increase in mean salivary pH before and after consuming gambir candy (p<0.05). It was concluded that consumption of candies containing gambir extract can maintain and increase salivary pH.